Are Internal Migrants in Albania Leaving for the Better? - Hagen-Zanker, Jessica; Azzarri, Carlo (2012)
Most studies on Albanian migration have focused on international migrants. This paper contributes to filling a gap in the literature by assessing the impact of internal migration on household well-being. The study draws on the Albania Living Standards Measurement Survey of 2005, with a focus on migrant households oversampled in peri-urban Tirana, who are compared with nonmigrant rural households. Various statistical procedures are used, yielding the following results: income improves through migration but consumption does not because of higher living costs. Moreover, migrant households in peri-urban Tirana live in poor dwelling conditions, are employed in irregular and unstable jobs, and experience health problems, especially in the early years of migration.